An Albumin-Binding Domain Peptide Confers Enhanced Immunoprotection Against Viral Myocarditis by CVB3 VP1 Vaccine - Gao, Yue; Yue, Yan; Xiong, Sidong (Frontiers in Immunology, 2021)
Coxsackievirus B3 (CVB3)-induced viral myocarditis is a common clinical cardiovascular disease without effective available vaccine. In this study, we tried to potentiate the immunoprotection efficacy of our previous CVB3-specific VP1 protein vaccine by introducing a streptococcal protein G-derived, draining lymph nodes (dLNs)-targeting albumin-binding domain (ABD) peptide. We found that compared with the original VP1 vaccine, ABD-fused VP1 (ABD-VP1) vaccine gained the new ability to efficiently bind murine albumin both in vitro and in vivo, possessed a much longer serum half-life in serum and exhibited more abundance in the dLNs after immunization. Accordingly, ABD-VP1 immunization not only significantly facilitated the enrichment and maturation of dendritic cells (DCs), induced higher percentages of IFN-γ+ CD8+ cells in the dLNs, but also robustly promoted VP1-induced T cell proliferation and cytotoxic T lymphocyte (CTL) responses in the spleens. More importantly, ABD-VP1 also elicited higher percentages of protective CD44hi CD62Lhi memory T cells in dLNs and spleens. Consequently, obvious protective effect against viral myocarditis was conferred by ABD-VP1 vaccine compared to the VP1 vaccine, reflected by the less body weight loss, improved cardiac function, alleviated cardiac histomorphological changes and an increased 28-day survival rate. Our results indicated that the ABD might be a promising immune-enhancing regime for vaccine design and development.